Surgical treatment of symptomatic patellofemoral malalignment: Do we need an ideal patellofemoral congruency to solve the symptoms? - Apostolović Milan; Vukčević Miodrag; Vučković Vladimir; Vukomanović Boris; Slavković Nemanja; Đuričić Goran; Antonijević Nebojša; Čučilović Oskar (Vojnosanitetski Pregled)
Background/Aim. The aim of this prospective nonrandomized study was to test functional results of different surgical strategies in the operative treatment of symptomatic patellofemoral malalignment. Our hypothesis was that immediate extensive surgery does not have serious advantage comparing to “step by step” procedure, regarding the main symptoms and functional end result. We wanted to check whether obtaining ideal surgical patellofemoral congruency is an essential prerequisite for subsidence of the major symptoms of patellofemoral malalignment. Methods. The study included 35 patients with patellofemoral malalignment who had persistant major symptoms: patellar pain and slipping, 3 months after nonoperative treatment. Divided into three groups, they all underwent the realignment surgery, but in different extent and sequence: immediate extensive surgery, step by step surgery, and only proximal realignment. Their overall functional scores as well as major symptoms were assessed at the beginning, after the surgery, and during the 3-years follow-up period and then, compared at the end. Results. There was no significant difference in the functional results among the groups, neither at the beginning (p = 0.1318) nor at the end of the study (p = 0.3996), but the results at the beginning compared to those at the end of the study showed a statistically significant difference in all three groups (p1 = 0.005062; p2 = 0.011719; p3 = 0.000352). The same result was in regard to the major symptoms. Conclusion. The study confirmed that insisting on immediate extensive surgery in order to achieve precise and complete congruency of the patellofemoral joint, did not prove its advantage over the less invasive, individual surgical approach concerning functional scores and major symptoms.